A redescription of the late Carboniferous trematopid Actiobates peabodyi from Garnett, Kansas. Issue 11 (10th February 2020) - Gee, Bryan M.; Reisz, Robert R.
Abstract: Dissorophoids are a diverse clade of predominantly Permo‐Carboniferous temnospondyls with a wide geographic distribution and broad ecological diversity. Each of the various dissorophoid clades first appears in the late Carboniferous, but their records are relatively sparse and fragmentary compared to those of the early Permian when dissorophoids reach their peak diversity and distribution, particularly in terrestrial environments where they are by far the most taxonomically diverse clade of non‐amniote tetrapods. This provides an impetus for further study of the late Carboniferous terrestrial dissorophoids in order to contextualize the early stages in the clade's radiation into terrestrial ecosystems. Here we present a redescription of the late Carboniferous trematopid Actiobates peabodyi from Kansas, USA, which is represented by a nearly complete skeleton and which represents the earliest occurrence of trematopids in North America. Only the skull was previously described, and the taxon has been largely overlooked in the context of early terrestrial dissorophoid evolution. Here, we provide an updated cranial description, the first postcranial description, and a discussion of the position of A. peabodyi in the context of olsoniform evolution. Our most significant finding is the characterization of postcranial anatomy that is highly similar to that of later trematopid taxa. This high degree of conservatism indicates that the earliest trematopids were already well adapted for terrestrial environments, and post‐Carboniferous radiations of olsoniforms may be attributed to an expansion of the dryland terrestrial environments in which these taxa already thrived, rather than to novel acquisition of adaptive features later in the clade's evolution.